Sex-Dimorphic Interactions of MAOA Genotype and Child Maltreatment Predispose College Students to Polysubstance Use - Fite, Paula J.; Brown, Shaquanna; Hossain, Waheeda A.; Manzardo, Ann; Butler, Merlin G.; Bortolato, Marco (Frontiers in Genetics, 2020)
Polysubstance use (PSU) is highly prevalent among college students. Recent evidence indicates that PSU is based on gene x environment (G×E) interactions, yet the specific biosocial factors underlying this problem remain elusive. We recently reported that lifetime use of tobacco and cannabis in college students is influenced by the interaction of the X-linked MAOA (monoamine oxidase A) gene and child maltreatment. Building on these premises, here we evaluated whether the same G×E interaction may also predict PSU in this population. Students of a large Midwestern university (n = 470; 50.9% females) took part in a computer survey for substance use, as well as childhood trauma exposure, using the Child Trauma Questionnaire (CTQ). DNA was extracted from their saliva samples and genotyped for MAOA variable-number of tandem repeat (VNTR) variants. Findings indicated that the highest number of substances were used by male students harboring low-activity MAOA alleles with a history of childhood emotional abuse. In contrast, female homozygous high-activity MAOA carriers with a history of emotional and physical abuse reported consumption of the greatest number of substances. Our results indicate that PSU among college students is influenced by the interaction of MAOA and child maltreatment in a sex-specific fashion. Further studies are warranted to understand the mechanisms of sex differences in the biosocial interplays underlying PSU in this at-risk group.